Evaluación de la factibilidad de emulsiones de extractos oleosos de nuez de palma de chambira (Astrocaryum chambira) (2017)
"In the aim of constructing the sustainable profile of use of Chambira palm, tests were carried out with the oily extracts of Chambira nut for the formulation of emulsions. Reverse (W/O) and Direct (O/W) emulsions were obtained with phase separation time between one and two hours. Mixing parameters of 15% wax, 80% water and 5% surfactant where used. The surfactant corresponds to 98% Span80 and 2% Tween20 for the direct emulsion and 99% Span80 and 1% Tween20 for the inverse emulsion. Mixing parameters such as gradual mixing of the hydrophilic phase on the lipophilic phase, stirring with dispermat gradually increasing from 500 to 1000 rpm and heating with a plate at 60ÀC, proved to be effective for the formulation of the emulsion. Phenomena of instability of cremation and flocculation were evidenced in the emulsions due to the significant difference of density between the phases." -- Tomado del Formato de Documento de Grado.